Autism in the School Context: The Importance of Social Insertion (Research, Society and Development, 2019)
This article is based on the evolution of the concept of autism over the years. Since 1943, described by Leo Kanner, to this day, by the DSM-V. Transiting by authors like Hans Asperger, Araújo, among others. Autism is described as a neurodevelopmental disorder characterized by deficits in communication and social interaction. In the school context we can observe how these difficulties present themselves and cause losses in their socio-educational development. With the aim of discussing the challenges of socializing the autistic child in school. For this, a qualitative and descriptive bibliographic study was carried out. It was concluded that for a better insertion of the autistic in the socio-school environment we conclude that a series of adaptations will be necessary, both in the environment and in the conscience of all who live with the children with the disorder, be they teachers or colleagues.